(untitled) (Philological Studies, 2019)
The article aims to present the meanings of conjunctions through their functions in different content relationships. It demonstrates the varying inter-dependence of conjunctions and predicators in coordination and subordination, especially drawing attention to the relationships between conjunctions of the same class and conjunctions within the same content relationship.